934PCirculating tumour DNA (ctDNA) utility as a biomarker for metastatic urothelial carcinoma (mUC). (1st October 2019) - Lavoie, J-M; Vandekerkhove, G; Annala, M; Taavitsainen, S; Sundahl, N L; Walz, S; Sano, T; Khalaf, D; Todenhöfer, T; Ost, P; Kollmannsberger, C K; Chi, K N; et al.
Abstract: Background: The therapeutic landscape for mUC is rapidly evolving, with the introduction of immune checkpoint inhibitors (CPIs) and targeted therapies providing new options. Prognostic and predictive biomarkers are urgently needed to facilitate clinical decision-making. In this setting, ctDNA is a non-invasive method for genomic profiling, but its clinical utility remains largely untested. Methods: Whole blood samples were collected for next-generation sequencing of leukocyte and cell-free DNA (cfDNA). Deep targeted sequencing was performed across a UC-specific custom 50-gene panel to a median unique read depth of 1040x for cfDNA. Clinical records were reviewed for baseline characteristics and outcomes. Results: From 12/2014 until 11/2018, 103 patients with mUC underwent blood collection for cfDNA analysis. Of these, 84 had detectable ctDNA. Baseline characteristics and outcomes are presented in the table below for the entire cohort, along with exploratory analyses for patients who received platinum-based chemotherapy or a CPI in the metastatic setting. For cases with ctDNA>1%, selected results based on the presence or absence of mutations (muts.) in TP53 and ERCC2, as well as tumour mutation burden (TMB), are included. Conclusions: In our mUC cohort, the presence of ctDNA fraction above median correlated with worse OS, while mutations in ERCC2 correlated with improved PFS for platinum-treated patients. These data support the further exploration and validation of ctDNA as a tool for biomarker development in mUC. Additional analyses will be presented for the entire 50-gene panel. Legal entity responsible for the study: The authors. Funding: Canadian Institutes of Health Research (CIHR) Bladder Cancer Canada (BCC). Disclosure: J. Lavoie: Honoraria (self): Astellas. N.L. Sundahl: Travel / Accommodation / Expenses: MSD; Travel / Accommodation / Expenses: Astellas; Travel / Accommodation / Expenses: Bayer; Travel / Accommodation / Expenses: BMS. D. Khalaf: Advisory / Consultancy: Bayer. T. Todenhöfer: Advisory / Consultancy: MSD; Advisory / Consultancy: Roche; Advisory / Consultancy: BMS. C.K. Kollmannsberger: Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Pfizer; Advisory / Consultancy: Sanofi; Advisory / Consultancy: Astellas; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: BMS; Advisory / Consultancy: Merck; Advisory / Consultancy, Travel / Accommodation / Expenses: Eisai; Honoraria (self), Advisory / Consultancy: Ipsen; Advisory / Consultancy: Janssen; Advisory / Consultancy: EMD Serono; Advisory / Consultancy: Roche. K.N. Chi: Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Sanofi; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Janssen; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Astellas; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Bayer; Advisory / Consultancy: Essa; Advisory / Consultancy: Amgen; Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Advisory / Consultancy, Research grant / Funding (institution): Roche; Research grant / Funding (institution): Tokai Pharmaceuticals; Research grant / Funding (institution): Lilly/ImClone; Research grant / Funding (institution): BMS; Research grant / Funding (institution): Merck. B.J. Eigl: Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Janssen; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Merck; Advisory / Consultancy: Zomanex; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Roche; Honoraria (self), Research grant / Funding (institution): Astellas; Honoraria (self), Research grant / Funding (institution): Pfizer. All other authors have declared no conflicts of interest.